PRAJURIT YANG PROFESIONAL MENUJU TNI MODERN PADA ERA REFORMASI - Lindra Kristiana; Paulina Siregar; Sambas Burhanudin (PPM Sdirjianbang Akademi Militer, 2024)
This article discuses about The Indonesian National Defense Forces (Tentara Nasional Indonesia/TNI) who has been experiencing a shift from praetorian military to profes-sional military because of fundamental change within Indonesian society after the end of the Soeharto’s regime in 1998 which is followed by a transition of power from New Order to reformed government. That shift can be seen through some issues related to territorial institutions, military business, and relation between TNI and The Ministry of Defense (Departemen Pertahanan). This paper argues that that shift and its related issues can be explained by patriot professional military thesis. This thesis combines certain aspects of Huntington’s old professionalism and Stepan’s new professionalism. As a patriot professional military TNI has professional characteristics as well as strong commitment to take a part in nondefense tasks according to decisions of civilian go-vernment. To become patriot professional military TNI needs to develop itself in a condition with objective civilian control that promotes military professionalism, and highly respects the civilian supremacy. This paper approached its problem with sociology of military, and made its inquiry with qualitative method.